BIOMETRIC INDICATORS OF NARROW-LEAVED LAVENDER DEPENDING ON THE APPLICATION OF GROWTH BIOSTIMULATORS IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Кусаковская, Наталия; Хомина, Вероника (Modern engineering and innovative technologies, 2022)
The purpose is to determine the best time for harvesting cuttings and to establish the influence of biostimulators of growth on rooting cuttings and the formation of biometric indicators of narrow-leaved lavender plants when grown in the Western Forest-St